ANALYSIS OF THE LEVEL OF TORCH INFECTION AMONG WOMEN OF FERTILE AGEIN SAMARKAND REGION - Yarmuxamedova M. Q.; Ne’matov H. A. (Web of Journals Publishing, 2024)
In the article, the rate of infection among women of reproductive age in Samarkand region is analyzed. The article is intended for information purposes, and no targeted epidemiological study of the prevalence of TORCH infections has been conducted in this region. The data obtained on the main pathogens included in the TORCH infection group are screening data and are used to assess the specific humoral response of the population.Purpose: to study the results of laboratory research on the determination of markers of TORCH-infections.Methods: 13 572 laboratory tests of blood serum samples from 1778 patients were performed. The research was conducted by IFA method.Results of research: Tests were performed in different age groups (0-80years) of male and female sex, assigned profile research on TORCH-infection.Of all the results obtained, the percentage of seropositive was 52,72%. The main component is the addition of IgG to herpes virus, rubella virus and cytomegalovirus, and the presence of antibodies IgG and IgM to toxoplasma infection is minimal.Extracts: Currently, laboratory diagnostics has sufficiently sensitive and highly specific test systems for the detection of TORCH-infection by serological methods, which was confirmed by the minimum percentage of "indeterminate" results for all classes and types of immunoglobulins.
Keywords: TORCH-infection, antibody, IFA, test-system.